Iron force constants of bridgmanite at high pressure: Implications for iron isotope fractionation in the deep mantle. (1st February 2021) - Wang, Wenzhong; Liu, Jiachao; Yang, Hong; Dorfman, Susannah M.; Lv, Mingda; Li, Jie; Zhu, Feng; Zhao, Jiyong; Hu, Michael Y.; Bi, Wenli; Alp, Ercan E.; Xiao, Yuming; et al.
Abstract: The isotopic compositions of iron in major mantle minerals may record chemical exchange between deep-Earth reservoirs as a result of early differentiation and ongoing plate tectonics processes. Bridgmanite (Bdg), the most abundant mineral in the Earth's lower mantle, can incorporate not only Al but also Fe with different oxidation states and spin states, which in turn can influence the distribution of Fe isotopes between Bdg and ferropericlase (Fp) and between the lower mantle and the core. In this study, we combined first-principles calculations with high-pressure nuclear resonant inelastic X-ray scattering measurements to evaluate the effects of Fe site occupancy, valence, and spin states at lower-mantle conditions on the reduced Fe partition function ratio ( β -factor) of Bdg. Our results show that the spin transition of octahedral-site (B-site) Fe 3+ in Bdg under mid-lower-mantle conditions generates a +0.09‰ increase in its β -factor, which is the most significant effect compared to Fe site occupancy and valence. Fe 2+ -bearing Bdg varieties have smaller β -factors relative to Fe 3+ -bearing varieties, especially those containing B-site Fe 3+ . Our models suggest that Fe isotopic fractionation between Bdg and Fp is only significant in the lowermost mantle due to the occurrence of low-spin Fe 2+ in Fp. Assuming early segregation of an iron core from a deep magma ocean, we find that neither core formation nor magma ocean crystallization would have resulted in resolvable Fe isotope fractionation. In contrast, Fe isotopic fractionation between low-spin Fe 3+ -bearing Bdg/Fe 2+ -bearing Fp and metallic iron at the core-mantle boundary may have enriched the lowermost mantle in heavy Fe isotopes by up to +0.20‰.